The rediscovery of Fritz Heider’s early social cognition: a person-centered perspective - Shang, Yaming; Dong, Da; Chen, Wei (Frontiers in Psychology, 2025)
In this article, we situate the social psychologist and philosopher Fritz Heider’s theory within what we call “early social cognition,” a historical approach preceding and radically differing from contemporary “social cognition.” By incorporating recent developments in issues such as perception, animacy, and social structures (networks), we reassess key aspects of Heider’s system to demonstrate their present-day significance. This analysis does not merely reiterate Heider’s ideas but shifts the methodological focus from his causal analysis of event attribution to a constitutive scientific explanation. In particular, we examine Heider’s early focus on the perceptual realism of the general object and his emphasis on the person-thing distinction. By engaging with contemporary developments on the animate-inanimate subcategorical distinction, we argue that Heider’s person-centered perspective may offer a unified theoretical framework for the construction of theories in social cognition.